Structural effects of cobalt-amine compounds on DNA condensation. - Deng, H (1999)
Light scattering and electron microscopy have been used to investigate the structural effects of the trivalent complexes hexaammine cobalt (III) chloride (Cohex), tris(ethylenediamine) cobalt(III) chloride (Coen), and cobalt(III) sepulchrate chloride (Cosep) on DNA condensation. These cobalt-amine compounds have similar ligand coordination geometries but differ slightly in size. Their hydrophobicity is in the order Cosep > Coen > Cohex, according to the numbers of methylene groups in these ligands. All of these compounds effectively precipitate DNA at high concentrations; but despite a lower surface charge density, Cosep condenses DNA twice as effectively as Coen or Cohex. UV and CD measurements of the supernatants of cobalt-amine/DNA solutions reveal a preferential binding of Delta-Coen over Lambda-Coen to the precipitated DNA, but there is no chiral selectivity for Cosep. Competition experiments show that the binding strengths of these three cobalt-amine compounds to aggregated DNA are comparable. A charge neutralization of 88-90% is required for DNA condensation. Our data indicate that 1) electrostatic interaction is the main driving force for binding of multivalent cations to DNA; 2) DNA condensation is dependent on the structure of the condensing agent; and 3) the hydration pattern or polarization of water molecules on the surface of condensing agents plays an important role in DNA condensation and chiral recognition.